Neuroblastoma RAS Viral Oncogene Homolog (NRAS) Is a Novel Prognostic Marker and Contributes to Sorafenib Resistance in Hepatocellular Carcinoma - Dietrich, Peter; Gaza, Anne; Wormser, Laura; Fritz, Valerie; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Neoplasia, 2019)
Inhibition of the RAS-RAF-ERK-pathway using sorafenib as a first-line and regorafenib as a second-line treatment approach is the only effective therapeutic strategy for advanced hepatocellular carcinoma (HCC). Recent studies suggest that wild-type KRAS and HRAS isoforms could majorly contribute to HCC progression and sorafenib resistance. In contrast, the role of neuroblastoma RAS viral oncogene homolog (NRAS) in HCC remained elusive. In this study, wild-type NRAS was found to be overexpressed in HCC cell lines, preclinical HCC models, and human HCC tissues. Moreover, NRAS overexpression correlated with poor survival and proliferation in vivo. However, siRNA-pool-mediated NRAS knockdown showed only slight effects on HCC proliferation, clonogenicity, and AKT activity. We determined that KRAS upregulation served as a functional compensatory mechanism in the absence of NRAS, which was overcome by combined inhibition of NRAS and KRAS in HCC cells. Furthermore, NRAS expression was elevated in sorafenib-resistant compared to nonresistant HCC cells, and NRAS knockdown enhanced sorafenib efficacy in resistant cells. In summary, NRAS appears to be a prognostic marker in HCC and contributes to sorafenib resistance. Regarding potential therapeutic strategies, NRAS inhibition in HCC should be combined with KRAS inhibition to prevent KRAS-mediated rescue effects.
CRIS-Team WoS Importer:2019-03-20